Biblical Archaeology 101: Storage and Staples in Biblical Israel - Frank, Tim (The Biblical archaeology review, 2022)
Securing and storing food was just as essential in biblical times as it is today. Across Israel, archaeologists have unearthed containers and installations used to store essential staples and foodstuffs, shedding light on everyday life in the biblical world.